White adipose tissue as a target for cadmium toxicity - Attia, Sarra Mohammed; Das, Sandra Concepcion; Varadharajan, Kavitha; Al-Naemi, Hamda A. (Frontiers in Pharmacology, 2022)
Cadmium (Cd) is a widespread heavy metal known as a toxic environmental pollutant. Cd exposure is threatening due to its bioaccumulation trait in living systems that exceeds 35 years without a beneficial biological role. Acute exposure to high Cd doses was reported to impact adipose tissue (AT) function adversely. The main aim of this study is to investigate the effect of low-dose chronic Cd exposure on the genes involved in adipose tissue (AT) functions. Adult male Sprague-Dawley rats were exposed to a low Cd dose (15 mg/kg B.W./day) for ten weeks. Then, three AT depots-subcutaneous AT (SUB-AT), abdominal AT (AB-AT), and retroperitoneal AT (REtrop-AT) were excised for Cd accumulation measures and gene expression analysis. Adiponectin and leptin gene expression levels were investigated as markers for adipocytes function and homeostasis. Our results showed that Cd accumulated in all the tested adipose depots, but SUB-AT was found to be the depot to most accumulate Cd. Also, it was exhibited that chronic exposure to low Cd doses altered the gene expression of adipocytokines. The levels of adiponectin and leptin mRNA expression were downregulated in all tested AT-depots after Cd exposure. The significant adverse effect on SUB-AT compared to other depots indicates different responses based on AT depots location toward Cd exposure. Collectively, these results suggest a toxic effect of Cd that influenced adipocyte function.